INTERNATIONAL EXPERIENCE IN RISK MANAGEMENT IN THE BANKING SECTOR IN THE CONTEXT OF ECONOMIC REFORMS - J.L.Saidov (Scholar Express Journals, 2024)
In the world practice, improving the efficiency of service provision through risk assessment in the banking industry in recent years remains one of the main problems causing serious difficulties. This article examines the international experience of implementing banking risks using various regulatory methods. In particular, examples of the financial situation of the banking system of countries such as the United Kingdom, France, the United States, and the Netherlands are given. The author also notes the possibility of using approaches and tools for a more complete risk assessment methodology in the banking sector
Keywords: banking system; commercial banks; supervisory authority; risk management